Newspaper vs. online advertising - Is there a niche for newspapers in modern advertising markets? - Nadine Lindstädt; Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
Newspapers have been experiencing declining circulation figures and advertising revenues for several years. Declining advertising figures, in particular, pose a threat to newspapers - this is especially severe in the U.S. where 73 per cent of newspapers' revenues are generated through advertising. Many companies have expanded their advertising expenditures to online. Consequently, there are concerns about online advertising substituting newspaper advertising - much the same as has long been feared with regard to readership. Both possible effects might pose a threat to the continuing existence of (print) newspapers. However, though the internet - compared to newspapers - offers a variety of advantages for advertising companies, substitution tendencies cannot be generalized. In particular, we argue that newspaper advertising offers great benefits for the retailing industry. Thus, we believe that retail advertising offers a niche for regional and local newspapers that can be expected to represent a sustainable segment of complementarity within the otherwise predominantly substitutional advertising markets. The paper substantiates this argument by applying the economic theory of advertising - specifically the differentiation between persuasive/complementary and informative advertising. The latter presents the reason for retailers to continue advertising in newspapers. We conclude that no complete substitution between newspaper and online advertising can be expected to take place in the foreseeable future.
Keywords: L82; A20; L13; M21; 330; media economics; advertising; competition; complementation; substitution; online